Analisis Keterlaksanaan Pendekatan Discovery Learning Terhadap Hasil Belajar Siswa SMA Negeri 1 Nimboran - Cartika Candra Ledoh; Elsi Sirampun; Ria Ristiani; Precilia Rafra (Departement of Mathematics Education, 2023)
This study aims to determine the teacher's ability to manage learning by applying the discovery learning model, to determine learning outcomes specifically on spiritual attitudes and social attitudes. This type of research is descriptive research, the sample in this study were X grade students of SMA Negeri 1 Nimboran which amounted to 30 people. The results of this study were that the teacher was able to manage learning activities by applying the discovery learning model at SMA Negeri 1 Nimboran which was indicated by an average score of 3.66 including in the good category, the completeness of the learning outcomes of spiritual attitudes using questionnaires and observations was declared complete with an average score of 92.68 and the completeness of the learning outcomes of social attitudes using questionnaires and observations was declared complete with an average score of 88.19.